1997
DOI: 10.1164/ajrccm.155.2.9032223
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of nitric oxide and vasoactive intestinal peptide on bronchoprotection against histamine in anesthetized guinea pigs.

Abstract: Vasoactive intestinal peptide (VIP) and nitric oxide (NO) are considered to be nonadrenergic, noncholinergic (NANC) inhibitory neurostransmitters in the airways. It seems likely that these neurotransmitters may be coreleased and act as functional antagonists against bronchoconstrictor stimuli. In the present study, we examined the synergistic effect of NO and VIP on bronchoprotection against histamine in anesthetized guinea pigs. The NO donor, S-nitroso-N-acetylpenicillamine (SNAP) significantly inhibited hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 15 publications
0
9
0
2
Order By: Relevance
“…Cholinergic tone is thought to be increased in asthma by several mechanisms, i.e., increased afferent stimulation by inflammation (27), abnormal muscarinic receptor expression (28), increased release of acetylcholine from cholinergic nerve ending (29), and decreased levels of neuromodulators that attenuate cholinergic neurotransmission (30). Nevertheless, the use of anticholinergics in asthma has been justified only in asthma exacerbations (3).…”
Section: Discussionmentioning
confidence: 99%
“…Cholinergic tone is thought to be increased in asthma by several mechanisms, i.e., increased afferent stimulation by inflammation (27), abnormal muscarinic receptor expression (28), increased release of acetylcholine from cholinergic nerve ending (29), and decreased levels of neuromodulators that attenuate cholinergic neurotransmission (30). Nevertheless, the use of anticholinergics in asthma has been justified only in asthma exacerbations (3).…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that VIP activates receptor‐linked Gα s and downstream adenylyl and/or guanylyl cyclase activation, resulting in stimulation of cyclic adenosine monophosphate (cAMP)‐dependent protein kinase A (PKA) and/or cGMP‐dependent protein kinase G (PKG) (2426). However, it has been suggested that half of the vasodilatory effects of VIP are mediated by nitric oxide (NO) signaling (2729). VIP also stimulates intracellular Ca 2+ signaling in some cells (3, 5, 6), including human nasal submucosal gland serous cells, where VIP also enhances the magnitude of cholinergic‐induced Ca 2+ signals (3).…”
mentioning
confidence: 99%
“…Подчеркивая значение этого меха низма бронхоконстрикции, Г.Б.Федосеев выделяет даже "холинергический вариант БА", описывая его клинические особенности [11]. Ряд механизмов, та ких как усиление стимуляции афферентных рецеп торов медиаторами воспаления [12], повышенное высвобождение ацетилхолина из холинергических нервных окончаний [13], ненормальная экспрессия мускариновых рецепторов посредством увеличения количества М3 рецепторов или уменьшения М2 ре цепторов [14], снижение уровня нейромодуляторов (вазоактивного кишечного пептида, оксида азота), тормозящих нейротрансмиссию [15], приводят к по вышению холинергического тонуса при БА, что оправдывает назначение в качестве бронхолитичес кой терапии антихолинергических препаратов. Кро ме того, было обнаружено, что у больных с генотипом Arg/Arg бронходилатирующий эффект ипратропия даже более выражен, чем сальбутамола [16].…”
Section: таблица 5 клинические данные исследуемых пациентовunclassified